Hybrid neighborhoods: From sandlots to social media - Karras, Dimitris; Koletsi, Maria; Vagias, Georgios (Homo Virtualis, 2020)
The rapid development of Information and Communication Technologies (ICT) along with the mass urbanization phenomenon have led to dramatic changes in the ways people create social bonds, form and understand communities and act collectively towards common goals. One important change is that locality and distance is no longer perceived as a key prerequisite for the development of social bonds. Local communities, traditionally based on social grouping by physical proximity, have been seriously affected by technological media (social media and applications). Socio-psychological research shows that the major impact of technology-based communication is the transformation of social bonds between members of local communities and the social capital they accumulate. Within this framework, the research project “GEITONIA” has a dual scope. On a theoretical level, to shed more light on the different ways and degrees local communities use social media and applications in everyday life. On an empirical level, to examine if and in what ways a local social medium mobile application, developed for neighborhoods, can help the understanding of the sense of community and re-strengthen the social cohesion among its members. The article is an attempt to provide a quick glance on the key concepts and theoretical background on which the research project is based.